Analisis Abnormal Return Saham pada Peristiwa Merger dan Akuisisi di Indonesia - Laurenza Sandra R. Ayu Putri; Ima Kristina Yulita; Aurelia M. Nisita Wardhani (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
This study aims to obtain empirical evidence related to market reactions indicated by abnormal returns around the time of the 2016-2019 merger and acquisition announcement. The population in this study are companies listed on the Indonesia Stock Exchange that have conducted mergers and acquisitions. The sampling technique uses purposive sampling, the data obtained by 12 companies, namely 3 companies do mergers and 9 companies make acquisitions. Data analysis techniques in this study were one sample test method Kolmogorv-Smirnov test, paired sample t-test test, and one sample t-test using SPSS application version 25. The results of this study showed: During the 11 days study period, there were average abnormal return negative that insignificant for 7 days and average abnormal return positive that also insignificant for 4 days around the announcement time of the company’s mergers and acquisitions. These insignificant test results prove that the market was not approved during the period before and after mergers and acquisitions.